2018
DOI: 10.1039/c8cp03574a
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable similarity of force induced dsRNA conformational changes to stretched dsDNA and their detection using electrical measurements

Abstract: We show the emergence of S-RNA under stretching in analogy to S-DNA and propose a method for its detection using electrical measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 61 publications
3
56
0
Order By: Relevance
“…Accordingly, charge transport in RNA can significantly differ from that in DNA and is worth thorough investigation. However, while multiple theoretical and experimental studies addressed charge transport in DNA [16][17][18][19], such studies for RNA [14,20,21] are rare. Very recently, it was shown that charge transport along the DNA molecule plays an important role in regulation of the replication process [18] and DNA repair [19], and disruption of DNA conductivity may cause severe diseases [22].…”
Section: Of 10mentioning
confidence: 99%
“…Accordingly, charge transport in RNA can significantly differ from that in DNA and is worth thorough investigation. However, while multiple theoretical and experimental studies addressed charge transport in DNA [16][17][18][19], such studies for RNA [14,20,21] are rare. Very recently, it was shown that charge transport along the DNA molecule plays an important role in regulation of the replication process [18] and DNA repair [19], and disruption of DNA conductivity may cause severe diseases [22].…”
Section: Of 10mentioning
confidence: 99%
“…dsDNA exhibits different force-extension regimes with Hookean behavior at low forces and a drastic elongation of its length at a force of 65 pN [1,6]. This is followed by an overstretching behavior where dsDNA transforms to a completely new structural phase-broadly described as a thermodynamically melted form (with broken Watson-Crick base-pairs) or a structurally intact base-pair stacking alignment in a ladder-like fashion (the so-called S-DNA) [6,[51][52][53].…”
Section: Structural Transitions In Dsdna Under Forcementioning
confidence: 99%
“…dsDNA has been studied in various conditions, such as unzipping, shearing, stretching, and under a torque, to mimic different biological scenarios [1]. These have provided increased insights to various interesting aspects of DNA such as emergence of S-DNA upon overstretching [5,10,51,52], modifications of DNA structural and mechanical properties under different environments such as drug intercalators [15 ], salts [17 ,46 ] and ionic liquids [26 ]. These information are the key inputs for DNA nanotechnological applications, enabling researchers to design various DNA nanostructures like DNA nanotubes [32,33 ] and DNA nanorobots for drug delivery [65], as well as in DNA nanoelectronics [51,52].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…tRNA and ribosomal RNA (rRNA) [15]. While multiple theoretical and experimental studies addressed charge transport in DNA [16][17][18][19], such studies for RNA [14,20,21] are rare. Very recently, it was shown that charge transport along the DNA molecule plays important role in regulation of the replication process [18] and DNA repair [19], and disruption of DNA conductivity may cause severe diseases [22].…”
Section: Introductionmentioning
confidence: 99%